Between absolutism and efficiency - Keating, Gregory C. (Revus (Ljubljana), 2019)
The author develops two lines of argument. One line responds to specific objections advanced by his critics and seeks to show that these objections do not undermine the claim that the safety and feasibility standards are rationally justifiable alternatives to cost-justification. This Reply leads, however, with a second line of argument. We are all-consequentialists and non-consequentialists, philosophers and economists-imprisoned in the grip of the debate between utilitarianism and its critics that dominated political philosophy in the latter half of the 20th century. Classical utilitarianism fell into disfavor because its commitment to maximizing utility may justify depriving minorities of basic rights whenever such restrictions promote the greatest net happiness. The cure for this fault is to make some basic rights "absolute"- to rule out some trade-offs entirely. The legacy of this debate is the conclusion that we must choose between "absolutism" and "efficiency". Unattractive as "efficient" trade-offs may be, the absolute prohibition of trade-offs is untenable when risks of physical harm are at issue. The safety and feasibility standards must fail because they are unacceptably absolutist. Once we shake ourselves free of this philosophical legacy we can see that these standards are standards for making trade-offs not for forbidding them and that the trade-offs they prescribe are plausible.
Keywords: absolutism; cost-benefit analysis; efficiency; negligence; precaution; priority of avoiding harm; responsibility; rights; risk; safety; trade-offs; utility; welfare